Sacubitril/valsartan compared to ramipril in high risk post myocardial infarction patients stratified according use of mineralocorticoid receptor antagonists: insight from PARADISE MI trial. (3rd October 2022) - Schou, M; Claggett, B; Fernandez, A; Filippatos, G; Granger, C; Jering, K; Maggioni, A; McCausland, F; Nunez Villota, J; Rouleau, J L; Mody, F G; Van Der Meer, P; et al.
Abstract: Background: Mineralocorticoid receptor antagonists (MRAs) reduce the risk of cardiovascular death or heart failure admission in patients with myocardial infarction (MI) and left ventricular systolic dysfunction (LVSD) combined with either heart failure (HF) or diabetes. Whether use of MRA and initiation of sacubitril/valsartan are safe and whether MRAs modify the effect of sacubitril/valsartan initiation in high-risk MI patients is unknown. Purpose: This analysis examined whether background treatment with a MRA modifies the treatment effect and safety of sacubitril/valsartan in patients with a MI and LVSD and/or pulmonary congestion. Methods: In the PARADISE MI Trial (Prospective ARNI vs. ACE inhibitor trial to DetermIne Superiority in reducing heart failure Events after Myocardial Infarction) N=5661 patients were randomized to either sacubitril/valsartan (97/103 mg twice daily) or ramipril (5 mg twice daily) within 7 days of their MI. The primary outcome in this analysis was the composite of worsening HF (HF hospitalization or outpatient worsening) or cardiovascular death evaluated by the clinical endpoint committee (CEC-adjudicated) or the investigators. Safety was defined as symptomatic hypotension, hyperkalemia >5.5 mmol/L or permanent drug discontinuation. Results: A total of 2338 patients (41%) were treated with an MRA and they were more often Caucasian (79% vs. 73%), had worse left ventricular ejection fraction (34±8 vs. 38±10%), a higher KILLIP Class (63% vs. 55% in class II or more) and a lower estimated Glomerular filtration rate (71 vs. 73 ml/min/1.73 m 2 ), than patients not taking an MRA. Age (63 years), sex (24% females), and frequency of diabetes (42%) did not differ. The treatment effect of sacubitril/valsartan compared with ramipril was similar in patients taking or not taking an MRA: hazard ratio (MRA): (95% confidence interval [CI]): 0.96 (0.77, 1.19) versus (95% CI: 0.87 (0.71, 1.05), respectively, for the primary endpoint (p value for interaction = 0.51) (CEC adjudicated) (Figure 1); similar findings were observed if investigator reported endpoints were evaluated (P=0.61 for interaction). Safety of sacubitril/valsartan compared to ramipril initiation was not changed by +/−MRA use, but an increase in symptomatic hypotension was observed (HR(MRA): 1.37 and HR: 1.39, P<0.001) in both groups (P=0.968 for interaction), whereas an increased risk of hyperkalemia or permanent drug discontinuation was not observed in the sacubitril/valsartan group (P>0.05 for all comparisons). Conclusions: As expected, patients taking MRAs had a higher risk. Use of a MRA did not modify the treatment effect and safety of initiation of sacubitril/valsartan compared to ramipril in the post MI setting in patients with LVSD and/or congestion. Our analyses support that sacubitril/valsartan and MRAs can be used simultaneously. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Novartis sponsored Randomized clinical trial